„Chyba w ten sposób toczy się ta ludzka komedia przez całe pokolenia drogą na Zachód i przez pustynie”. Paraboliczność w kinie braci Coen - Żyto, Kamila (Załącznik Kulturoznawczy, 2022)
The Coen brothers stylized films, full of quotations and borrowings, are for many scholars the quintessence of a postmodern game with remnants, interpretive openness, and ambiguity. This fact does not incline to look in these films for the rules governing the world or human existence what is typical of parabolic thinking. The article is an attempt to demonstrate that the makers of the Oscar-winning Fargo (Fargo, 1996) often use in their work elements, tricks, or strategies typical of a traditional parabola, though their films may often be read as its contemporary invariants. Numerous Coens’ films bear the hallmarks of parabolic texts, even if in this case one cannot speak of a parabola as a genre. The messages they contain are never unambiguous and are not intended to educate. However, owing to their enigmatic nature, they encourage viewers to search for extra meanings.